When Societal Structural Issues Become Patient Problems: The Role of Clinical Ethics Consultation. Issue 5 (11th October 2018) - Milliken, Aimee; Jurchak, Martha; Sadovnikoff, Nicholas
Abstract: The debate about health insurance coverage and the related issue of unequal access to health care turn on fundamental questions of justice, but for an individual patient like DM, the abstract question about who is deserving of health insurance becomes a very concrete problem that has a profound impact on care and livelihood. DM's circumstances left him stuck in the hospital. A satisfactory discharge plan remained elusive; his insurance coverage severely limited the number and type of facilities that would accept him; and his inadequate engagement in his own rehabilitation process limited discharge options even further. Despite extensive involvement with the psychiatry, social work, physical therapy, and occupational therapy teams, DM consistently made "bad" decisions. He repeatedly refused antibiotics and did not consistently work with rehab services to improve his strength and mobility. Although the clinicians wanted to provide him with the best care possible, he often seemed unwilling to do the things necessary to achieve this care—or perhaps his depression rendered him unable to do so. He also tended to take out his frustration on staff members caring for him. All of this was, in turn, very frustrating for the staff. It may be easy, however, to make too much of DM's role, to see his choices as more important than his circumstances. A major goal of the ethics consultants was to reframe DM's predicament for the staff members involved in his care .